MENINGKATKAN MINAT BELAJAR KELAS 10 PADA MATA PELAJARAN SEJARAH DENGAN METODE GAME BASED LEARNING DI MAN 2 KARAWANG - Alifa Fadiya, Nasyia; Aprila Saraswati, Adinda; Rahman Dirta, Aldi; Aini Farida, Nur; Makbul, M. (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to increase class 10 stuldents' interest in learning in the sulbject of History throulgh the application of the Game Based Learning (GBL) method. The GBL method is ulsed with the hope of making the learning process more interactive, interesting and fuln for stuldents. This research ulses a classrooml action research (PTK) design which consists of several cycles. Each cycle involves planning, imlplemlentation, oblservation, and reflection. Data was collected throulgh oblservation, learning interest qulestionnaires, and interviews with stuldents. The research resullts show that the application of the GBLL mlethod significantly increases stuldents' interest in learning. Stuldents show increalsed alctive palrticipaltion, enthulsialsml alnd interest in the historicall mlalteriall bleing talulght. The conclulsion of this resealrch is thalt the Galmle BLalsed Lealrning mlethod is effective in increalsing clalss 10 stuldents' interest in lealrning in the sulblject of History, so it is recomlmlended for ulse als al lealrning straltegy in schools.